Single Leg Speed Hop Pengaruh Single Leg Speed Hop Terhadap Daya Ledak Otot Tungkai Pada Pesilat - Achwan Achwan; Siti Najiahtul Hasanah; Ari Sudarsono (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2022)
ABSTRACT Background: The explosive power of leg muscle is the ability to exert maximum power in the shortest possible time. Muscle explosive power is important for a fighter in locking, swinging, dropping, punching, kicking and avoiding attacks from unexpected angles and directions. Ways to increase muscle explosive power include plyometric training and one of them is single leg speed hops. Research Objectives: To determine the effect of single leg speed hop pliometric exercises on increasing the explosive power of limb muscles in pesilat members at SMPN 1 Parung. Research Methods: The design of this study was quasi-experimental with